PENGARUH KONSELING ASUHAN KEFARMASIAN PADA RESPONDEN DIABETES MELLITUS II UNTUK PENINGKATAN KEPATUHAN MINUM OBAT DALAM PENGENDALIAN GLUKOSA DARAH DI RUMAH SAKIT SIDOARJO - Priyono, Tridoso Sapto Agus; Siswidiasari, Arifani; Wati, Henni (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
The purpose of the study was to determine the compliance and glucose levels of patients DM II and the effect of counseling pharmaceutical care on compliance and glucose levels of patients DM II Outpatient at Sidoarjo hospital with a sample of 47 patients. The research method is quantitative with descriptive analysis techniques, related of counseling pharmaceutical care on adherence and glucose levels of patients DM II and the relationship between adherence and glucose levels of patients DM II. The compliance is obtained from the results of the questionnaire, while glucose levels are obtained from measurements before and after counseling using univariate tests with descriptive techniques to see a description of the characteristics of patients DM II and bivariate tests are carried out with normality tests and correlation tests. The results was a significant effect of providing counseling pharmaceutical care on compliance and glucose levels of patients DM II. The provision of counseling pharmaceutical care can significantly reduce the glucose levels of patients DM II, and obtained a value of p = 0.000. The average fasting glucose level of patients was 190.98 ± 74.85, while after counseling, it dropped to 73.79 ± 97.48, and the patient's glucose level 2 hours after eating was 250.70 ± 92.36 while after counseling, the average patient's glucose level 2 hours after eating decreased to 218.47 ± 113.21. The conclusion of the study is that counseling pharmaceutical care can improve compliance and reduce the glucose levels of outpatients DM II at the Sidoarjo hospital.